A SURVEY OF THE VEHICLE ROUTING PROBLEM IN-HOME HEALTH CARE SERVICES - Ettazi Haitam (University of Kragujevac, 2021)
In a transport Logistics problem, there can be a multitude of constraints that come into play such as vehicle/depot capacity constraints, time constraints… in this paper we will see first the works which relate mainly to the context of logistics in the home care and services. then we will details the main works existing related to routing problems that have similarities to the field we are interested in. in third, we will see the various and several resolution approaches such as exact, approximate or even hybrids resulting from these of methods from combinatorial optimization and operational research whose effectiveness has been proven on the logistics problem of transport in general. This study allows us to have a general overview of research opportunities not still explored. Therefore, we expose and investigate the problems addressed in the literature, to identify new emerging research perspectives in this context.